Internalisasi Pendidikan Karakter dalam Meningkatkan Moral Anak pada Kurikulum Merdeka - ana puspita; Gustiana Yuantini; Yessika Destiana Lahabu; Ilmiah Sholikhah Oktafiani (Program Studi Pendidikan Islam Anak Usia Dini, 2025)
Character education has a strategic role in shaping children's personalities from an early age, especially in the context of PAUD). conducted to determine all the values ??????of character education at Aisyiyah Bustanul Athfal Kindergarten. The Merdeka PAUD curriculum provides a great opportunity to integrate character values ??????through a flexible, competency-based and child-centered learning approach. This research aims to examine strategies for internalizing educational character in implementing the Independent PAUD Curriculum and exploring the challenges and opportunities faced by educators in this process. Using a qualitative descriptive approach, data was collected through literature studies, interviews, and observations of learning practices in PAUD. The results of the research show that the internalization of character values ??????such as honesty, responsibility, tolerance, and cooperation can be done through integration in play activities, project-based learning, and daily habits. A holistic approach involving educators, parents and the surrounding environment is the key to the success of this process. However, the challenges faced include educators' limited understanding of the implementation of the Independent Curriculum, limited facilities and infrastructure, and lack of support from parents. This article recommends increasing training for educators and strengthening collaboration between schools, families and communities to support optimizing the character of education in early childhood.